Complex hallucal interphalangeal joint dislocation with incarcerated sesamoid: percutaneous reduction with K-wire and literature review - Sajeev, Suraj; Bharadwaj, Amit (International Journal of Research in Orthopaedics, 2026)
Irreducible dislocation of the hallucal interphalangeal (IP) joint is an uncommon injury, often complicated by incarceration of the sesamoid–plantar plate complex. While traditional management has relied on open reduction with or without sesamoid excision, minimally invasive approaches are gaining traction. This report presents a rare case of Miki type 2 IP joint dislocation with sesamoid interposition in a 22-year-old male who sustained a dorsiflexion injury while playing badminton barefoot. Initial closed manipulation converted the pattern to type 1, resulting in an elongated, stiff toe. Under general anaesthesia, a 2-mm Kirschner wire (K-wire) was inserted medially into the IP joint and advanced dorsally to plantarly to disengage the incarcerated sesamoid. An audible click signified successful reduction, and stability was confirmed through 30° of passive dorsiflexion. The joint was immobilized with an extension-blocking thermoplastic splint for three weeks. The patient returned to full activity by two months and remained asymptomatic at one-year follow-up. A systematic review identified 31 reported cases of hallucal IP dislocation. Type 2 injuries with sesamoid entrapment were consistently resistant to closed reduction; while early literature favoured open approaches, recent reports demonstrate the efficacy of percutaneous or ultrasound-guided techniques. This case supports percutaneous K-wire manipulation as a safe, minimally invasive alternative to open reduction, offering tactile mechanical advantage and a reduced risk of chondral injury. Percutaneous reduction under true lateral fluoroscopic guidance provides a tissue-preserving solution with excellent functional outcomes when combined with early recognition of the injury pattern.